Listening still - Griffin, Anne, 1969- (St. Martin's Press, 2022)
"From Anne Griffin, the bestselling author of When All is Said, comes Listening Still, a refreshing new novel about a young woman who can hear the dead-a talent which is both a gift and a curse. Jeanie Masterson has a gift: she can hear the recently dead and give voice to their final wishes and revelations. Inherited from her father, this gift has enabled the family undertakers to flourish in their small Irish town. Yet she has always been uneasy about censoring some of the dead's last messages to the living. Unsure, too, about the choice she made when she left school seventeen years ago: to stay or leave for a new life in London with her charismatic teenage sweetheart. So when Jeanie's parents unexpectedly announce their plan to retire, she is jolted out of her limbo. In this captivating successor to her much-lauded debut, When All Is Said, Anne Griffin portrays a young woman who is torn between duty, a comfortable marriage, a calling she both loves and hates and her last chance to break free. Listening Still is a heartachingly honest look at what we give up and what we gain when we choose to follow our heart"--